1993
DOI: 10.1007/bf00795373
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of late potential in patients with duchenne muscular dystrophy

Abstract: The relationship between late ventricular potentials (LP) and myocardial ischemic changes or ventricular arrhythmias was investigated in patients with Duchenne muscular dystrophy (DMD). Twenty-six DMD patients aged 10-33 years (mean 18.2 years) and 27 age-matched healthy volunteers were studied. Ventricular arrhythmias were detected by 24-h Holter ECGs and LPs were determined using signal-averaged ECGs. In DMD patients filtered QRS duration, late duration, and low-amplitude signal under 40 microV were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Myocardial fibrosis, the second leading cause of death in DMD [3], [7], [8], occurs in more than 96% of DMD hearts and causes cardiac dysfunction that leads to heart failure. Furthermore, fibrotic lesions in the myocardium can act as foci of ventricular arrhythmias that are common and often fatal in DMD patients [7], [9], [10]. Additionally, fibrosis of limb muscles causes permanent, immobilizing contractures that impede ambulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial fibrosis, the second leading cause of death in DMD [3], [7], [8], occurs in more than 96% of DMD hearts and causes cardiac dysfunction that leads to heart failure. Furthermore, fibrotic lesions in the myocardium can act as foci of ventricular arrhythmias that are common and often fatal in DMD patients [7], [9], [10]. Additionally, fibrosis of limb muscles causes permanent, immobilizing contractures that impede ambulation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also the root mean square voltage of the last 40 ms QRS was decreased. Patients with late potentials had more frequently ST-T depression, and ventricular arrhythmias than patients without [16]. In another study of 84 DMD patients, the prevalence of late potentials was 28% [56].…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
“…Late potential parameters were closely related to left ventricular wall motion abnormalities. In a controlled study on 26 DMD patients, late potentials were found in 31% [16]. The filtered QRS duration, late duration and increase in low-amplitude signals <40 µV were significantly prolonged.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 99%
See 1 more Smart Citation
“…It affects also the heart (myocyte degeneration, fibrosis and fatty infiltration), impairing ventricular repolarization, causing autonomic dysfunction, QTc prolongation and increase of QT dispersion, as an independent risk factor for ventricular arrhythmias of Lown grade III or higher [86][87][88]. Late ventricular potentials were reported in patients with Duchenne muscular dystrophy (31%), indicating the presence of a substrate for reentry ventricular arrhythmias, associated with local myocardial fibrosis, and identifying patients at high risk for sudden cardiac death [89]. Cardiac involvement was also mentioned in other dystrophinopathies, due to the replacement of myocardium by connective tissue or fat, but it remains subclinical in Duchenne and Becker muscular dystrophy [86].…”
Section: Cerebrogenic Arrhythmias and Ventricular Arrhythmia Risk In mentioning
confidence: 99%